2001
DOI: 10.1006/jcss.2001.1779
|View full text |Cite
|
Sign up to set email alerts
|

Protocols for Asymmetric Communication Channels

Abstract: In this paper we examine the problem of sending an n-bit data item from a client to a server across an asymmetric communication channel. We demonstrate that there are scenarios in which a high-speed link from the server to the client can be used to greatly reduce the number of bits sent from the client to the server across a slower link. In particular, we assume that the data item is drawn from a probability distribution D that is known to the server but not to the client. We present several protocols in which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…Multiplicative approximations have the potential of yielding codes that can be represented within o(n) bits. Adler and Maggs [1] showed it generally takes more than (9/40)n 1/(20c) lg n bits to store a prefix code with average codeword length at most cH(P ). Gagie [19,20,21] showed that, for any constant c ≥ 1, it takes O n 1/c log n bits to store a prefix code with average codeword length at most cH(P ) + 2.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiplicative approximations have the potential of yielding codes that can be represented within o(n) bits. Adler and Maggs [1] showed it generally takes more than (9/40)n 1/(20c) lg n bits to store a prefix code with average codeword length at most cH(P ). Gagie [19,20,21] showed that, for any constant c ≥ 1, it takes O n 1/c log n bits to store a prefix code with average codeword length at most cH(P ) + 2.…”
Section: Related Workmentioning
confidence: 99%
“…Our specific contributions are the following. 1. In Section 3 we show that it is possible to store an optimal prefix code within O(n log max ) bits, where max = O(min(n, log N )) is the maximum length of a code (Theorem 1).…”
Section: Introductionmentioning
confidence: 99%
“…Strategies for searching in trees have also potential application to asymmetric communication protocols [1,3,15,22,31]. In this scenario, a client has to send a binary string x ∈ {0, 1} t to the server.…”
Section: Introductionmentioning
confidence: 99%
“…In order to benefit from this discrepancy, both parties agree on a protocol to exchange bits until the server learns the string x, trying to minimize the number of bits sent by the client (though other factors, e.g., the number of rounds should also be taken into account). In one of the first protocols [3,22], at each round the server sends a binary string y and the client replies with a 0 or 1 depending on whether y is a prefix of x or not. Based on the client's answer, the server updates his knowledge about x and sends another string if he has not learned x yet.…”
Section: Introductionmentioning
confidence: 99%
“…In 1998 Adler and Maggs [1] showed it generally takes more than (9/40)n 1/(20c) log n bits to store a prefix code with expected codeword length at most cH(P ), where H(P ) is P 's entropy and a lower bound on the expected codeword length. (In this paper we consider only binary codes, and by log we always mean log 2 .)…”
Section: Introductionmentioning
confidence: 99%